Penggunaan Metode Tanya Jawab Untuk Membangun Keaktifan Siswa Pada Pembelajaran Jarak Jauh - Fitri Yani Harefa; Widiastuti Widiastuti (Jurnal Ilmiah Wahana Pendidikan, 2023)
The activeness of students in class is important for the success of learning in class. Student activity can be seen through the learning process carried out in class. In fact, grade VI students at an elementary school in Nias showed inactivity when distance learning was implemented. Therefore, we need a method that can build student activity in learning, one of which is the question and answer method. The purpose of this study is to describe the use of the question and answer method to build student activity in distance learning. The method used is descriptive qualitative. The results showed that the question and answer method was successful in building student activity in distance learning. Thus it can be concluded that the question and answer method can be applied in the classroom to build student activity during distance learning. The advice given is that teachers need to be more creative in applying the question-and-answer method, for example in the form of quizzes or in the form of games.